ANALYSIS OF HEALTH ASSESSMENT WITH CAMEL METHOD IN AN NISA'S COOPERATIVE, BLITAR CITY - Ulya Nur Isnaini (State Islamic Institute (IAIN) Tulungagung, 2020)
This article will focus on discussing the health level of An Nisa 'Cooperative to assess the performance of cooperatives based on the regulations of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06 / PER / DEP.6 / IV / 2016. This type of research is a type of quantitative research. The data used are financial reports and also the results of interviews from management cooperatives as primary data, and secondary data as supplementary and reinforcing data. While the data analysis technique uses data analysis techniques using the camel method and cooperative deputy regulations. The results of this study indicate that the health of the An Nisa cooperative is included in the category of supervision, therefore the Blitar Regency UMKM cooperative office will provide guidance by the cooperative. The purpose of fostering unhealthy cooperatives is to help cooperatives to improve and develop the knowledge and skills that cooperatives already have to become even better.